Entre o Estado e o capital: ferrovia e territorialidade em Sorocaba - Mauá Filho, Clovis Hiran Fuentes (Universidade Federal de São Carlos, 2019)
This paper aims to understand the ongoing process of degradation of railway structures in the city of Sorocaba, inaugurated after the privatization of 1998 and which led to the abandonment and ruin of various railway structures in the city, as well as the interests involved in the recent dispute over the new social uses of this railway heritage. It was sought to link the (past and present) relationship between the railroad and the city to the formation of local territoriality, by studying the historical development of the railroad in Sorocaba and its role in urban production. To this end, support was sought through David Harvey's theory of uneven geographical development, as well as his tripartite spatial theory. For the understanding of territorial issues, an analysis was composed involving several authors, with emphasis on Michel Foucault, Jean Gottmann, Claude Raffestin and David Harvey. Both to understand the railroad as an artificer in the production of urban space and to analyze its degradation in Sorocaba, it was sought to understand through its characteristics as fixed capital, based on the Marxist definition and David Harvey's reading about the geographical impacts of this form of capital. In order to analyze the territorial interests and disputes involved, the understanding of the relations between state and capital was prioritized, giving a brief history about the railway development in the country with emphasis on this relationship, and the theoretical support of Giovanni Arrighi, David Harvey and Nicos Poulantzas. Finally, a survey was made of the current situation of the railway structures in Sorocaba, defining actors and interests related to the railway in the city, through photographic study, analysis of official documents and journalistic material.
Between state and capital: railroad and territoriality in Sorocaba
Keywords: Ferrovia; Sorocaba; Produção do Espaço Urbano; Territorialidade; Estado; Capital Fixo; Railway; Urban Space Production; Territoriality; State; Fixed Capital; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA